2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7320213
|View full text |Cite
|
Sign up to set email alerts
|

Accurate measurement of respiratory airflow waveforms using depth data

Abstract: Respiratory disorders are a very common and growing health problem. Signal waveforms of respiratory airflow and volume may indicate pathological signs of several diseases and, thus, it would be important to measure them accurately. Currently, devices used in respiration measurements are mostly obtrusive in nature interfering with the natural respiration patterns. We used a depth camera for the continuous measurement of respiratory function without contact on a subject. We propose a novel calibration method whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Correlation of 0.96 was reported against a spirometer for estimating respiratory volume. Similar to [8], Seppanen et al [9] used the first generation Kinect to estimate the respiration rate (of healthy subjects) by generating respiratory airflow waveform using several models from depth sensor data. The best coefficient of determination (R 2 ) between the spirometer signal and the estimated airflow signal was reported as 0.93.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Correlation of 0.96 was reported against a spirometer for estimating respiratory volume. Similar to [8], Seppanen et al [9] used the first generation Kinect to estimate the respiration rate (of healthy subjects) by generating respiratory airflow waveform using several models from depth sensor data. The best coefficient of determination (R 2 ) between the spirometer signal and the estimated airflow signal was reported as 0.93.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Aoki et al [9] and Yu et al [10], computed the subject's chest volume variations in depth sequences to estimate the airflow signal, and respectively reported 0.98 and 0.96 correlation against their groundtruth. Seppanen et al [11] estimated airflow signal using multi-input-singleoutput models fed by the data acquired using a depth sensor. Their best correlation against a spirometer was R 2 = 0.93.…”
Section: Related Workmentioning
confidence: 99%
“…This work is licensed under a Creative Commons Attribution 3.0 License. For more information, see http://creativecommons.org/licenses/by/3.0/ [5], [6], [8], [12], [13] and structured light depth sensors [7], [9]- [11] and RGB video cameras [14], [15]. Some of these are briefly considered in Section II.…”
mentioning
confidence: 99%
“…Eight subjects were included in the trial, in which they performed different breathing styles while being measured using a depth camera and spirometer. The study concluded that it was possible to measure the TV and the RR very accurately [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not easy for a patient to use measuring devices for spirometry, impedance pneumography, or inductance plethysmography correctly, because they are primarily designed for clinical or research centers. Hence, they are not applicable for everyday use for home monitoring due to the complexity of the devices, their high cost, their need for skilled operators, and, in some cases, their limited portability [9,10]. Additionally, these devices require the user to be in direct contact with the equipment in an obtrusive manner, which interferes with natural respiration [10].…”
Section: Introductionmentioning
confidence: 99%